Students’ expectations in EFL classroom: A case study at management department of a private university in Yogyakarta - Efit Eriani; Bambang Widi Pratolo; Yuyun Nailufer; Devi Martha Astuti (Universitas Ahmad Dahlan)
Students have their own expectations in the teaching and learning process in the classroom. Students’ expectations are also one of the important things that the lecturer should know and do to get a good outcome. The purpose of this study is to identify students’ expectations in the teaching and learning process in English class. This study uses a qualitative method. To collect the data, the researchers used observation and semi-interview methods. Observation was carried out to investigate the students’ and lecturer’s activities in the classroom, while interview was used to examine the students’ expectation related to the use of English in the future, the content of English subject, and their learning style. Seventh students in the first semester of the undergraduate Management Department became the participants of this study. The result of the study shows that all students expect that they would learn all skills of English as well as grammar and pronunciation. They also believe that they would get good jobs if they could master English well.